The Sexual Assault of Older Women: Criminal Justice Responses in Canada - Grant, Isabel; Benedet, Janine (McGill Law Journal / Revue de droit de McGill, 2016)
This article examines sexual violence against older women, a problem that has been largely hidden from view in the societal and legal discussion of sexual assault. The article identifies a significant disconnect between the social science description of sexual assault against older women, on the one hand, and the available case law, on the other. The social science literature suggests that older women are most likely to be sexually assaulted by somebody they know and that a disproportionate number of the sexual assaults against older women take place within care facilities. The case law, however, paints a very different picture of sexual violence against older women—a majority of the reported cases involve women attacked in their homes by strangers in the context of a robbery or home invasion. We argue that this portrayal of sexual violence against older women in the case law resembles that of the case law of sexual assault against younger women thirty years ago, before the women’s movement brought acquaintance and spousal sexual assault into the public eye. We conclude that these types of sexual assaults continue to be under-reported for older women, and we explore some of the reasons for the failure of the criminal justice system to respond to this group of complainants.